1, 4-Conjugate addition/esterification of ortho-quinone methides in a multicomponent reaction. Issue 83 (2nd October 2018) - Chen, Renjie; Liu, Yu; Cui, Sunliang
Abstract : A novel 1, 4-conjugate addition/esterification of ortho -quinone methides in a multicomponent reaction has been developed for facilely accessing 3, 3-diarylpropanamides. Abstract : A novel 1, 4-conjugate addition/esterification of ortho -quinone methides in a multicomponent reaction has been developed. In this protocol, numerous carboxylic acids, ynamides and in situ generated ortho -quinone methides could assemble rapidly to constitute this process for the synthesis of functionalized 3, 3-diarylpropanamides with sufficient structural diversity. Furthermore, the products could be transformed to an array of compounds.